The effect of the analgesic combination ibuprofen and caffeine on serum levels of alanine aminotransferase in Wistar rats - Muhammad Fadel Yudawa; Donna Hermawati; Faizah Fulyani; Astika Widy Utomo (Indonesian Journal of Biomedicine and Clinical Sciences, 2026)
The combination of ibuprofen and caffeine is effective in single-dose oral dosageforms to manage moderate or severe pain in acute postoperative pain. The useof ibuprofen has been reported to result in hepatotoxicity with a hepatocellularform. In contrast, caffeine has been reported to reduce fibrosis in liver tissueby several mechanisms. Gold standard examination to monitor hepatotoxicitycan be done by checking ALT and AST enzymes in the blood. Therefore, it wasnecessary to examine the levels of ALT to assess the opposite effect of these twodrugs on liver function, which had never been studied before. The aim of thestudy was to determine the effect of the analgesic combination of ibuprofenand caffeine on serum ALT levels of male Wistar rats. This was an experimentalpost-test only control group design using 24 Wistar rats divided into 4 groups, 1control groups and 3 intervention groups. ALT levels were measured using theendpoint enzymatic assay method (Berthelot) with a spectrophotometer. Datawere analyzed using SPSS, and a p <0.05 was considered significant. The resultsof the One-Way ANOVA test showed a significant difference (p=0.002) betweenall groups. The results of the Post-Hoc test showed a significant difference in thecontrol to the group 2 (IBU) treatment (p=0.026), the control to the group 4 (IBUCAF)treatment (p=0.029), the group 2 (IBU) treatment to the group 3 (CAF) treatment(p=0.001), and the group 3 (CAF) treatment to the group 4 (IBUCAF) treatment (p=0.001). However, there was no significant difference in the control to the group 3(CAF) treatment (p=0.150) and the group 2 (IBU) treatment to the group 4 (IBUCAF)treatment (p=0.955). In conclusion, co-administration of caffeine and ibuprofendid not potentiate hepatotoxicity compared with ibuprofen monotherapy, despitecaffeine independently could induced significant hepatic injury.